Five-year publication rate of clinical presentations at the open and closed American shoulder and elbow surgeons annual meeting from 2005–2010 - Kay, J. (J Exp Orthop, 2016)
BACKGROUND: The purpose of this study was to evaluate the five-year publication rate of papers presented at both the open and closed American Shoulder and Elbow Surgeons’ (ASES) annual meetings from 2005 to 2010. METHODS: Online abstracts of the presentations at the open and closed ASES annual meetings were independently screened for clinical studies and graded for quality using level of evidence. The databases PubMed (MEDLINE), Ovid (MEDLINE), and EMBASE were comprehensively searched for full-text publications corresponding to these presentations and any paper published within five years of the presentation date was counted. RESULTS: Overall, 131/266 papers corresponding to the meeting presentations were identified for a five-year publication rate of 49.2 %. Sixty two (48 %) of the papers were published in The Journal of Shoulder and Elbow Surgeons, 23 (18 %) were published in The American Journal of Sports Medicine, and 20 (16 %) were published in The Journal of Bone and Joint Surgery. The mean patient sample size included in presentations with a subsequent full-text publication was higher (154; standard error =27) than the presentations not published (93; standard error = 13) (p = 0.039). There was no correlation (p = 0.248) between the publication rate and the level of evidence of the presentations. CONCLUSIONS: The publication rate of presentations at ASES meetings from 2005 to 2010 is similar to that reported from other orthopaedic meetings. Studies with large sample sizes should continue to be encouraged, and high quality presentations must consistently be followed up with full-text manuscript preparation in order to maximize the future clinical impact.